PODCASTING AS AN EDUCATIONAL TOOL: PODCASTING AS AN EDUCATIONAL TOOL - I.Xalmuratov, I.Xalmuratov (Журнал иностранных языков и лингвистики, 2025)
The field of education is fast changing in the present digital age thanks to the love of technology. It is absolutely important in determining how teachers teach and how pupils pick knowledge. Among the several technology resources, podcasts have shown to be a useful and easily available tool for English language instruction. For teachers as well as students, these audio-based materials provide authenticity, flexibility, and involvement that go beyond mere tools.